Modern technologies of education of persons with disabilities: study guide - Salnikova O. D. (Ставрополь, СКФУ, 2023)
The manual reveals the technological aspects of the education of persons with disabilities and disabilities (the use of assistive, information and commu-nication, health-saving, psychocorrective, gaming, digital technologies in the framework of the educational process, as well as distance and e-learning tech-nologies, the possibility of implementing the principles of individualization and differentiation, pedagogical control and evaluation of learning outcomes based on them). The manual outlines the achievements of theory and practice in the field of the use of special equipment and software, digital and network resources and platforms in working with people with disabilities and disabilities. It is intended for students studying in the field of training 44.03.03 Special (defectological) education; it can be addressed to teachers-defectologists and other teachers working with people with disabilities and disabilities